Econometric analysis of volatile art markets - Fabian Y. R. P. Bocart; Christian M. Hafner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
A new heteroskedastic hedonic regression model is suggested which takes into account time-varying volatility and is applied to a blue chips art market. A nonparametric local likelihood estimator is proposed, and this is more precise than the often used dummy variables method. The empirical analysis reveals that errors are considerably non-Gaussian, and that a student distribution with time-varying scale and degrees of freedom does well in explaining deviations of prices from their expectation. The art price index is a smooth function of time and has a variability that is comparable to the volatility of stock indices.
Keywords: C14; C43; Z11; 330; volatility; art markets; hedonic regression; semiparametric estimation; Kunst; Preis; Kunsthandel; Volatilität; Hedonischer Preisindex; Nichtparametrisches Verfahren; Schätzung; Welt